Profile Of Sexually Transmitted Diseases In And Around Lucknow - Jaiswal A K; Baveja S; Chatterjee M; Verma R; Sah R L (Wolters Kluwer Medknow Publications, 2002)
A retrospective study was undertaken from the year 1988 to 1998 to study the pattern of sexually transmitted diseases in and around Lucknow. Among 1890 patients examined, chancroid predominated followed by syphilis, gonorrhoea, genital warts, herpes genitalis, LGV and non-specific urethritis. The incidence of donovanosis was the lowest.